A Study of Risk Factors Predicting School Disruption in Children and Youth Living in Ontario. (September 2021) - Sun, Li; Semovski, Valbona; Stewart, Shannon L.
School disruption (SD) places students at risk of early school departure and other negative psychological outcomes. Based on the data derived from a sample of Ontario children and youth, this study aims to identify risk factors associated with SD among 1, 241 school-aged students. A logistic regression model revealed that substance use, family functioning, Attention Deficit/Hyperactivity Disorder and experiencing bullying, significantly predicted SD. Substance use and family functioning resulted in the largest contributions to SD when holding other variables constant. This study provides supporting evidence of risk factors predicting SD and suggests that mental health and school personnel should consider family functioning and substance use in particular, when creating interventions to decrease premature school termination.